Tinjauan Yuridis Genosida (Genocide) Dalam Perspektif Hak Asasi Manusia Berdasarkan Pengadilan Internasional - I Putu Rama Aditya Prapta; I Nyoman Gede Sugiartha; I Nyoman Sutama (Fakultas Hukum Universitas Warmadewa, 2024)
Every human being is born with their own religion, ethnicity and culture. Violence in groups that want to eliminate other groups is called the crime of genocide. In connection with this, how is the regulation of genocide in human rights courts in an international perspective? and how is the settlement of genocide events in international courts? This research uses a normative research type. The regulation of genocide in international law has been regulated by the 1948 genocide convention in Article 2 and Article 3 and was first memorialized in the 1998 Rome Statute Article 6. the settlement of genocide uses peaceful settlement and forced settlement. Peaceful settlements, such as negotiations, mediation, conciliation overseen by the United Nations if the settlement does not work effectively then a forced settlement is carried out through an international court.